Perkembangan Komunikasi Bisnis di Era Digital: Tinjauan Literatur 2015-2023 - Mustamin; Murteza Ahmadinejad; Putri Damia Desiavera; Rizma Ayu Pratama; Mada Aditia Wardhana (Shofanah Media Berkah, 2026)
The development of digital technology has brought significant changes to business communication practices in various organizations. These changes affect how organizations manage information, coordinate work activities, and establish relationships with stakeholders. This article aims to examine the evolution of business communication in the digital era during the period 2015–2023 through a literature study of relevant scientific journal articles and academic books. The literature was analyzed using content analysis to identify patterns and trends in the development of business communication. The results of the study show a shift in business communication from a one-way pattern to more interactive and strategic communication, in line with the increasing use of digital media and online communication platforms. In addition, the post-COVID-19 pandemic conditions accelerated the implementation of remote communication and virtual collaboration, which had an impact on work patterns, organizational culture, and managerial roles. These developments confirm that business communication no longer functions solely as a means of conveying information but has become an important part of decision-making and achieving organizational goals in the digital era.